Relevance of single-nucleotide polymorphism to the expression of resistin gene affecting serum and gingival crevicular fluid resistin levels in chronic periodontitis and type 2 diabetes mellitus: A randomized control clinical trial - Pranita Avinash Rode; Rajashri Abhay Kolte; Abhay Pandurang Kolte; Hemant Jyotiswarup Purohit; Charu Ram Ahuja (Wolters Kluwer Medknow Publications, 2019)
Aim: The present study is aimed to investigate whether single-nucleotide polymorphism (SNP) of resistin gene (RETN) at −420 and +299 sites, is associated with resistin levels in serum and gingival crevicular fluid (GCF) in periodontally healthy, chronic periodontitis (CP) with and without type 2 diabetes mellitus (T2DM) patients. Materials and Methods: Serum and GCF samples were procured from all the 60 patients (twenty in each group) of the three study groups i.e., periodontally healthy (Group I), CP (Group II) and CP with T2DM patients (Group III) to analyze resistin levels using enzyme-linked immunosorbent assay test and clinical parameters were assessed at baseline and at 3 months after scaling and root planing (SRP). RETN polymorphism at −420 and +299 was genotyped by polymerase chain reaction-restriction fragment length polymorphism technique. Results: Patients with SNP −420 and +299 were positively correlated with increased serum and GCF resistin levels in Group II and Group III patients. SRP led to substantial reduction in the serum and GCF resistin levels. Conclusion: These findings are suggestive of a biologic link between resistin, periodontal diseases, and periodontal diseases with T2DM and RETN SNP at −420 and +299 in imparting increased resistin levels in inflammatory and diabetic conditions.